The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/157803
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Vogt-Koyanagi-Harada Disease and Sympathetic Ophthalmia

Abstract: Vogt-Koyanagi-Harada disease (VKH) and sympathetic ophthalmia (SO) are types of T-cell mediated autoimmune granulomatous uveitis. Although the two diseases share common clinical features, they have certain differences in gender predilections. VKH classically has been reported as more prevalent in females than males, yet some studies in Japan and China have not found differences in gender prevalence. Male patients have a higher risk of chorioretinal degeneration, vitiligo, and worse prognosis. Conversely, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 61 publications
0
20
0
1
Order By: Relevance
“…50 Long-term sequelae include choroidal neovascularization (CNV), sub-retinal fibrosis, and cataracts. 48, 51 Similar to other uveitic conditions with systemic involvement, gender affects the prognosis; 50 a male VKH patient is significantly more likely to have a poorer visual outcome than a female patient. An Indian group found that 37.5% of their male VKH patients had vision worse than 20/80, compared to only 3.3% of their female VKH cohort.…”
Section: Female Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
See 3 more Smart Citations
“…50 Long-term sequelae include choroidal neovascularization (CNV), sub-retinal fibrosis, and cataracts. 48, 51 Similar to other uveitic conditions with systemic involvement, gender affects the prognosis; 50 a male VKH patient is significantly more likely to have a poorer visual outcome than a female patient. An Indian group found that 37.5% of their male VKH patients had vision worse than 20/80, compared to only 3.3% of their female VKH cohort.…”
Section: Female Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
“…52 The reason for the poorer male visual outcomes is unclear, though female sex hormones and HLA-DR genes have been associated with the female predisposition to the disease. 50, 53-55 …”
Section: Female Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…VKH is also common among females, while SO doesn't show any sexual predilection. SO is more common in young age due to trauma and in old age due to increased frequency of surgeries [7]. The inciting event is also different, usually, a penetrating ocular injury in SO.…”
Section: Discussionmentioning
confidence: 99%